Nutrition-Sensitive Factors Associated with the Stunted Growth of Under-Five Children with Infections in Rural Eastern Indonesia - Danal, Paskaliana Hilpriska; Hepilita, Yohana; Wea, Lidwina Dewiyanti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Nutrition-sensitive factors, such as infections, are indirect contributors to inadequate nutrient absorption. This study aims to identify the nutrition-sensitive factors associated with stunted growth among under-five children attending a public health center due to infection-related problems. A cross-sectional design was used, involving 47 children who visited the public health center in July 2022. Participants were recruited using purposive sampling. Data were collected using questionnaires, a microtoise, and the WHO growth chart. Bivariate analysis was performed using the Chi-square test, while multivariate analysis employed binary logistic regression. The results showed that 35 children had normal growth, while 12 were stunted. The most common nursing diagnosis was ineffective airway clearance (36.2%). Among the nutrition-sensitive factors, household water supply was the most dominant factor associated with stunted growth (OR = 42.317; p = 0.038). Poor access to clean water, mediated by infection, can hinder the linear growth of children.